Sorting growing-finishing pigs by weight fails to improve growth performance or weight variation - O’Quinn, P.R.; Swanson, J.C.; Musser, R.E.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A trial was conducted to determine the effects of sorting pigs by body weight at placement on growth performance and weight variation at finishing. Unsorted pigs and heavy sorted pigs had higher ADG than medium or light sorted pigs. By the end of the trial, final body weights ranked in the following descending order: heavy sorted, unsorted, medium sorted, and light sorted. Final weights of unsorted pigs were heavier than the average final weight of all sorted pigs. Additionally, differences in body weight variation were not detectable by the end of the study. These data suggest that sorting pigs uniformly by weight to pens has little effect on final variability in individual body weights and placing pigs into pens regardless of weight may increase the amount of pork produced from a system and reduce turnaround time in barns.
Keywords: Swine; Growing-Finishing pigs; Sorting; Growth performance; Weight variation